(untitled) (Analysis in Theory and Applications, 2023)
In this paper, by making use of Divergence theorem for multiple integrals, we establish some integral inequalities for Schur convex functions defined on bodies B⊂R^n that are symmetric, convex and have nonempty interiors. Examples for three dimensional balls are also provided.